THE EFFECT OF PARENTAL SUPPORT AND INTRINSIC MOTIVATION ON SELF-EFFICACY OF VOCATIONAL HIGH SCHOOL STUDENTS IN MEDAN The Impact of Parental Support and Intrinsic Motivation on the Self-Efficacy of Vocational School Students in Medan - Melda Susanti Sihite (RADJA PUBLIKA, 2024)
This study aims to examine the influence of parental support and intrinsic motivation on the self-efficacy of students at SMK Sultan Iskandar Muda Medan. A quantitative correlational method was employed using multiple linear regression analysis. A total of 220 students were selected through purposive sampling. The instruments used included Likert-type scales for parental support, intrinsic motivation, and self-efficacy. The analysis revealed that both variables had a positive and significant effect on self-efficacy (p < 0.05), with a simultaneous contribution of R² = 81.8%. These findings highlight the importance of social support and internal motivation in fostering students' self-confidence, particularly in academic contexts.